Taxonomic study on Afrotropical Osoriinae (Coleoptera: Staphylinidae). Status of Mimogonellus Fagel and Madegassosorius Scheerpeltz - Sapieja, Mateusz; Jałoszyński, Paweł (Zootaxa, 2024)
Among Afrotropical genera of Osoriini, Madegassosorius Scheerpeltz is exceptionally poorly defined. Although later authors maintained this genus, they restricted its diagnostic features and distinguish it from the apparently highly similar Mimogonellus Fagel merely by the structure or presence of the lateral pronotal carinae and the elytral adsutural striae. A comprehensive survey of specimens belonging to most world genera of Osoriini suggested that these characters may be variable within the genus and therefore of weak taxonomic value. In order to test this hypothesis, the type species of Madegassosorius and Mimogonellus were studied in detail, as well as dozens of additional specimens belonging to this unclearly defined group. As a result, Madegassosorius syn. n. is placed as a junior synonym of Mimogonellus, and the latter genus is redefined and redescribed. A lectotype is designated for Mimogonus leleupi Cameron, the type species of Mimogonellus. The synonymization of Madegassosorius with Mimogonellus results in one case of secondary homonymy, and Mimogonellus longipennides nom. n. is proposed as a replacement name for Mimogonellus longipennis (Coiffait, 1979) comb. n. (ex Madegassosorius), nec Mimogonellus longipennis Fagel, 1960.